The Genetic Code Kit: An Open-Source Cell-Free Platform for Biochemical and Biotechnology Education - Williams, Layne C.; Gregorio, Nicole E.; So, Byungcheol; Kao, Wesley Y.; Kiste, Alan L.; Patel, Pratish A.; Watts, Katharine R.; Oza, Javin P. (Frontiers in Bioengineering and Biotechnology, 2020)
Teaching the processes of transcription and translation is challenging due to the intangibility of these concepts and a lack of instructional, laboratory-based, active learning modules. Harnessing the genetic code in vitro with cell-free protein synthesis (CFPS) provides an open platform that allows direct manipulation of reaction conditions and biological machinery to enable inquiry-based learning. Here, we report our efforts to transform the research-based CFPS biotechnology into a hands-on module called the “Genetic Code Kit” for implementation into teaching laboratories. The Genetic Code Kit includes all reagents necessary for CFPS, as well as a laboratory manual, student worksheet, and augmented reality activity. This module allows students to actively explore transcription and translation while gaining exposure to an emerging research technology. In our testing of this module, undergraduate students who used the Genetic Code Kit in a teaching laboratory showed significant score increases on transcription and translation questions in a post-lab questionnaire while students who did not participate in the activity did not. Students also demonstrated an increase in self-reported confidence in laboratory methods and comfort with CFPS, indicating that this module helps prepare students for careers in laboratory research. Importantly, the Genetic Code Kit can accommodate a variety of learning objectives beyond transcription and translation and enables hypothesis-driven science. This opens the possibility of developing Course-Based Undergraduate Research Experiences (CUREs) based on the Genetic Code Kit, as well as supporting next-generation science standards in 8-12th grade science courses.